"ORO-GASTROENTEROLOGY", A TOPIC SUITED FOR PROFESSIONAL ORIENTATION? - Gheorghe Bălan; Dana Elena Mitrică; Silvia Cristina Țone; Adriana Bălan (Romanian Society of Oral Rehabilitation, 2015)
It is no doubt that during the last years, medicine and medical knowledge engaged in a process of hyperspecialization and intense focusing towards core details related to various pathological aspects. On the other hand, it is because of this orientation towards details that new bio-clinical relationships were established. One of these medical fields of interference is the relationship between digestive and oral diseases. Our aim is to explore the possibility of perceiving this pathological relationship as a new direction for professional orientation. Although the clinical basis regarding the cohesion of the two has been emphasized by the literature for many years by now, many aspects related to the aetiology and pathology of certain conjunct diseases are to be defined by detailed bio-chemical, cellular and molecular methods of investigation. Future doctors, but also the medical seniors could choose to explore this scientific domain, as it offers plenty of research directions and topics yet not fully understood.